An investigative study into post-molding shrinkage of plastic molded parts using different injection molding machines - Mok, Lum Yew. (2008)
Injection molding process is an established technique commonly used to produce plastic parts. The ability to control the material behavior and direct the flow into the mold holds the key towards producing good and consistent plastic parts. This task is made harder by the heterogeneous nature of the material and the process imperfections. This resulted in parts rejection requiring numerous production trial runs before the final set of parameter setting is adopted. Various design rules for both part and mould have therefore been established aimed at minimizing the number of parts rejection and trial runs. Appropriate sets of process parameters for molding of various types of plastics are also identified. Such efforts have greatly helped to reduce the process complexity thereby leading to its proliferation use.